CRITICALLY ANALYSING THE IMPACT OF AI BASED MARKETING ON THE RETAIL SECTOR IN INDIA - Ghosh, Uttam Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The introduction of “Artificial Intelligence” or “AI” has revolutionised the India retail market. Its integration in the marketing strategies has created a profound impact making it an essential topic of study. Several technologies of AI are involved in this process. It includes, “machine learning”, “predictive analysis” and “language processing” technology, which has helped the retailers optimise and automate their processes. It has also resulted in better decision making, and thereby improved the customer interactions. The current study aims to analyse the “effects of AI” in the Indian retail markets. This study, additionally tries to highlight the various opportunities created and the associated challenges that arise. The current study also focuses on the current mechanisms of adaptation to “AI based technology”. It would therefore help in a better understanding of both the benefits and challenges of “AI integration”. For this study, a “mixed methods” approach has been taken. Therefore, both “qualitative” and “quantitative” methods have been considered. The findings provide a comprehensive view of the “AI integration” in marketing. AI has helped the retailers to effectively increase “customer interaction” with the help of “predictive analytics” and has helped automate the marketing campaigns. Additionally, this study has identified several barriers to the adoption of AI. The associated “high costs”, and the concern for “data security” have been identified as top concerns of the retailers in the Indian market. Additionally, the study has revealed that the effects of AI on the “small and medium enterprises” (SMEs) of India is significant. It has led to them having long term “socio-economic” effects on their businesses. However, AI as a tool in the Indian retail sector has significant potential. Overcoming certain barriers would help the market reach its optimal potential. In this paper, additionally, the research gaps are also highlighted.